2015
DOI: 10.1111/rda.12652
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Prenatal and Neonatal Anti‐Androgen Flutamide Treatment on Aquaporin 5 Expression in the Adult Porcine Ovary

Abstract: The growth of ovarian follicles is accompanied by fluid-filled antrum formation. Water movement within the follicular wall is predominantly transcellular via membranous water channels named aquaporins (AQPs). Androgens are important regulators of mammalian folliculogenesis, and their prenatal and/or neonatal deficiency affects female fertility in adulthood. Therefore, this study was performed to determine whether gestational or neonatal exposure to the anti-androgen flutamide influences androgen-dependent AQP5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…Aquaporins facilitate water transport and are expressed in GCs (40), and testosterone stimulated the swelling of porcine GCs in hypotonic culture medium, an effect that was reversed by flutamide, suggesting that aquaporins are sensitive to androgen (41). A recent study by the same group confirmed that follicles from pigs that were exposed to flutamide in utero expressed less Aqp5 messenger RNA and protein, demonstrating that androgen could potentially stimulate aquaporin expression leading to antrum formation (42). …”
Section: Discussionmentioning
confidence: 98%
“…Aquaporins facilitate water transport and are expressed in GCs (40), and testosterone stimulated the swelling of porcine GCs in hypotonic culture medium, an effect that was reversed by flutamide, suggesting that aquaporins are sensitive to androgen (41). A recent study by the same group confirmed that follicles from pigs that were exposed to flutamide in utero expressed less Aqp5 messenger RNA and protein, demonstrating that androgen could potentially stimulate aquaporin expression leading to antrum formation (42). …”
Section: Discussionmentioning
confidence: 98%
“…Recently, Grzesiak et al. () revealed that maternal and neonatal exposure to anti‐androgen flutamide leads to decreased AQP5 expression in ovarian follicles of adult pigs. Moreover, presence of the oestrogen‐response element was confirmed in the promoter region of the AQP2 (Zou et al., ) and AQP5 (Kobayashi, Takahashi, Miyagawa, Watanabe, & Iguchi, ) genes, and androgen‐response element in the promoter of AQP5 gene (Moehren, Denayer, Podvinec, Verrijdt, & Claessens, ).…”
Section: Discussionmentioning
confidence: 99%
“…According to Grzesiak et al. (), supernatants containing 20 μg of total protein were mixed with loading buffer (62.5 m m Tris–HCl pH 6.8, 2% SDS, 25% glycerol, 0.01% bromophenol blue, 5% β‐mercaptoethanol) and warmed at 99.9°C for 3 min. After denaturation, samples were loaded into 12% SDS‐polyacrylamide gel, and proteins were separated by electrophoresis under reducing conditions.…”
Section: Methodsmentioning
confidence: 99%
“…Whereas, the presence of AQP5 mRNA in porcine ovarian follicles was reported recently by Grzesiak et al (2016). In that study diminished AQP5 mRNA and protein expressions within pre-antral and large antral follicles of adult pigs were presented.…”
Section: Discussionmentioning
confidence: 99%